Forensic linguistic evidence in Indonesian courtrooms: a study of language use in criminal verdicts - Wahyu Beny Mukti Setiyawan (Indonesian Journal of Linguistics and Legal Discourse, 2026)
Background: Language in Indonesian criminal verdicts functions not only as a medium of legal reasoning but also as a mechanism for constructing institutional authority and shaping public perceptions of justice. Objective: The aim of this study is to analyze how language in verdict texts constructs legal facts, interprets testimonies, and reproduces ideological frameworks in Indonesian courtrooms. Method: This research employs a qualitative design using forensic discourse analysis, speech act theory, and critical linguistic analysis on a purposive corpus of thirty verdicts sampled from the Supreme Court directory between 2020 and 2025. Results: The results reveal three key findings: first, passive voice and nominalizations dominate narrative construction, obscuring agency while reinforcing judicial neutrality; second, testimonies are strategically represented through denials, assertions, and commissives, yet frequently reframed in indirect speech that diminishes defendants’ agency; third, ideological expressions such as legitimizing formulae, stigmatizing labels, and religious appeals permeate verdicts, projecting institutional authority and moral legitimacy. These findings indicate that verdict texts are not ideologically neutral but discursive instruments that shape legal and cultural realities. Implication: This study’s implications underscore the need for critical awareness and reform in judicial writing practices to ensure transparency, protect defendants’ rights, and strengthen trust in Indonesia’s legal system. Novelty: This study elucidates how judicial language in Indonesian verdicts operates as a discursive mechanism that simultaneously structures legal reasoning, reconfigures agency, and reinforces institutional and ideological authority.